Retaining Non-EU Immigrants in Rural Areas to Sustain Depopulated Regions: Motives to Remain - Elisete Diogo (Societies, 2024)
Rural areas face multiple challenges. Among these are population decline and the attendant economic and social problems, namely demographic issues. Although the factors that draw immigrants to other countries are known, comprehending the factors that result in immigrants remaining in rural areas after their arrival could support informed local policies and practices. The purpose of the study is to explore the motivations that shape immigrants’ intentions to stay in Alentejo, a depopulated region in Portugal. The research questions are as follows: What motivates immigrants to remain in depopulated regions in Portugal? Furthermore, what contributions can practitioners and immigrants make to local policies and practices? Practitioners (n = 8) and non-European Union immigrants (n = 15) living in this region were interviewed between 2020 and 2021. The empirical data were analyzed using the MaxQDA software. The results indicated that the intention to remain in rural areas arises from a progressive process: this is a process that immigrants experience that motivates them to stay there long-term. The factors influencing the process include four components described throughout this work: (1) Instrumental and material motivations; (2) Emotional and social motivations; (3) Motivations based on the quality of life; and (4) Motivations based on the political dimension. The conclusions highlight the implications for policies and practices, suggesting more investment into rural regions to reverse the depopulation trend.